An investigation of the self-related concepts and foreign language motivation of young Deaf and hard-of-hearing learners in Hungary - Csizér, Kata; Kontra, Edit H.; Piniel, Katalin (Studies in Second Language Learning and Teaching, 2015)
In recent years increased attention has been given in applied linguistics to the learning processes of various groups of special needs (SN) students, especially to those whose achievement is impeded by dyslexia or other learning difficulties. However, students with sensory impairment, particularly those who are Deaf or severely hard of hearing (HOH), seem to have remained on the periphery of second language acquisition (SLA) research although they constitute a highly interesting group both from a linguistic as well as a cultural point of view. Since the best approach to understanding how this special minority handles foreign language learning is by first exploring their so-called individual differences, a nationwide research project was launched in Hungary to investigate students’ language learning beliefs, motivation, strategy use and motivated learning behavior. As part of that project, the present paper intends to detail how self-related concepts of hearing impaired students at eight different SN schools an be described. In order to gain an in-depth understanding, a mixed-method research design was employed. First, a barrier-free instrument was used to measure learner variables among 105 14-19-year-old Deaf and HOH learners. Then 31 individual interviews were conducted with selected students using maximum variety sampling. The quantitative data indicate that Deaf and HOH (D/HH) learners lack pronounced, well-developed and detailed future ideal L2 selves and corresponding visions to guide their learning. Another important finding is the paramount importance of language learning experience for our D/HH participants. Based on the analysis of the qualitative data, we can conclude that students’ language learning experiences are largely shaped by the choice of language used as the medium of education, the intensity and content of the English classes as well as how far students internalize extrinsic motives.